Purification and molecular characterization of a novel mannose‐specific lectin from Dioclea reflexa hook seeds with inflammatory activity. Issue 4 (14th October 2015) - Pinto‐Junior, Vanir R.; Correia, Jorge L. A.; Pereira, Ronniery I.; Pereira‐Junior, Francisco N.; Santiago, Mayara Q.; Osterne, Vinicius J. S.; Madeira, Juliana C.; Cajazeiras, João B.; Nagano, Celso S.; Delatorre, Plinio; Assreuy, Ana M. S.; Nascimento, Kyria S.; et al.
Abstract : A novel lectin present in Dioclea reflexa seeds (DrfL) was discovered and described in this study. DrfL was purified in a single step by affinity chromatography in a Sephadex G‐50 column. The lectin strongly agglutinated rabbit erythrocytes and was inhibited by α ‐methyl‐d ‐mannoside, d ‐mannose, andd ‐glucose. The hemagglutinating activity of DrfL is optimum at pH 5.0–7.0, stable up to 50 °C, and dependent on divalent cations. Similar to other lectins of the subtribe Diocleinae, the analysis by mass spectrometry indicated that DrfL has three chains ( α, β, and γ ) with masses of 25 562, 12 874, and 12 706 Da, respectively, with no disulfide bonds or glycosylation. DrfL showed inflammatory activity in the paw edema model and exhibited low cytotoxicity against Artemia sp. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : A new mannose‐specific lectin from Dioclea reflexa Hook seeds (DrfL) was purified and partially characterized. DrfL toxic effect was evaluated against Artemia sp. DrfL elicits acute inflammation via lectin domain mediated by nitric oxide.